A new approach to monitoring farmer prices: Method and an application to Malawi - Baulch, Bob; Kok, Seng Kiong; Jolex, Aubrey (Informa UK Limited, 2024)
This paper proposes a new approach to monitoring farmer prices in low-income developing countries. This crowdsourcing approach involves broadcasting radio jingles inviting farmers to report the prices and locations at which they sold their crops to a toll-free call centre, with weekly prizes to incentivize reporting. An application to Malawi illustrates the feasibility of this approach in a setting where internet connectivity is limited but mobile phone coverage is reasonable. The majority of farmers reporting sold to assemblers or small traders and received substantially less than official minimum farm gate prices. Non-parametric analysis shows that farmer prices vary according to bargaining power and sales volume but not by distance to the point of sale. These findings may be explained by the fragmented and monopsonistic nature of food markets in Malawi, and farmers’ mode of transport to the point of sale.